The Relationship Between Wrist Flexibility and Hand Reaction with Drive Stroke in Table Tennis - Awaluddin, Awaluddin; Sahabuddin, Sahabuddin (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
This study aims to determine the relationship between wrist flexion and hand reaction with drive strokes in tennis games. This research is a type of descriptive research. The population of this study is all students of SMP Negeri 40 Makassar with a research sample of 80 male students selected by random sampling. The data analysis technique used is a correlation and regression analysis technique using the SPSS Version 21.00 system at a significant level of 95% or ? 0.05. Starting from the results of data analysis, this study concludes that: There is a significant relationship between wrist flexion and drive stroke in tennis games, it is proven that the value of ro = 0.845 (P < ? 0.05); There was a significant relationship between hand reaction and drive stroke in tennis, it was proven that the value of ro = 0.865 (P < ? 0.05); There was a relationship between wrist flexion and hand reaction with drive strokes in tennis, proving the value of Ro = 0.910 (P < ? 0.05).